EDITORS' PREFACE. (4th September 2015) - Clarke, Peter D.; Questier, Michael C.
Abstract : The current volume brings together contributions from two separate editors. The first is a collection of texts edited by Peter Clarke that evidence Cardinal Thomas Wolsey's legatine powers to grant dispensations and other papal graces and his exercise of these powers during the 1520s in Henry VIII's realm. The second is a text edited by Michael Questier. It takes the form of glosses on and suggested readings of the Elizabethan statute law which imposed treason penalties on Catholic clergy who exercised their office in reconciling to Rome (i.e. absolving from schism and heresy) and on those who availed themselves of this sacramental power. The rationale for linking these contributions in a single volume is threefold. First, both generally concern Catholicism in Tudor England, especially the authority of Catholic clergy there both before and after the break with Rome. Secondly and more specifically, they regard the role of these clergy as agents of papal authority in Tudor England. Wolsey was appointed as a papal legate in 1518 and obtained legatine powers from successive popes on a scale unparalleled in pre-Reformation England, notably to grant dispensations, and he exercised these dispensing powers there extensively; he was thus the papal agent par excellence in Tudor England on the eve of the Reformation. The Elizabethan 'tolerationist' text, by contrast, seeks to deny that Catholic clergy necessarily functioned as agents of papal authority. They were not, therefore, all without exception traitors to the queen, even though one literal reading of the statute book might give the impression that this was what the State had meant. Instead, so this manuscript claimed, the statutes themselves could be read in such a way as to imply that the legislators themselves accepted that the Catholic clergy's priestly functions did not depend exclusively on papal supremacy (unlike Wolsey's legatine status) or even a malign anti-popish understanding of the papacy as a legal and ecclesiastical entity. Therefore the exercise of their faculties could not automatically be interpreted as treasonable. Coincidentally Wolsey's activity as a papal agent led to him being attainted him with treason, and although the charge did not relate to his dispensing powers, four years after Wolsey's fall Henry VIII forbade his subjects to petition Rome or its agents for the kinds of graces Wolsey had issued. He established the Faculty Office to issue such graces instead, and its authority depended on royal, not papal, supremacy. Both contributions, therefore, concern the relationship between Catholic clergy and supreme authority in the English Church, wherever this was deemed to lie. Thirdly, both contributions illuminate the limits of the law and flexibility in interpreting and applying it. Wolsey's graces in effect limited the operation of canon law: his dispensations suspended it in specific instances, notably regarding marriage and ordination; and he also granted licences permitting activity that it normally forbade, such as clergy not residing in their benefices. The 'tolerationist' text implies, although with arguments which at times seem rather specious, that the Elizabethan State was, even in its more draconian utterances, to some extent drawing in its horns. Both contributions, therefore, concern apparently binding law which might be relaxed in Tudor England with regard to Catholic clergy (as well as laity in the case of Wolsey's papal graces).